Experimental and theoretical investigations on sensing and dynamic characteristics of PVDF thin film. (19th November 2020) - Lin, Yu-Chih; Huang, Yu-Hsi; Ma, Chien-Ching; Chang, Chun-Kai
Abstract: This research investigates both the steady-state and transient dynamic characteristics of polyvinylidene fluoride (PVDF), which is one of the most commonly used piezoelectric polymers. In steady-state vibration, the visible resonant mode fringe patterns are obtained using the amplitude-fluctuation electronic speckle pattern interferometry experiment, and the point-wise displacement data are measured by laser Doppler vibrometer–dynamic signal analysis. Finite element analysis is also performed, and the numerical results are compared with the experimental ones for the steady-state vibration. In a transient dynamic experiment, the history of dynamic impact generated by a steel ball is measured by the PVDF, and the experimental results are compared with the theoretical results obtained by the Hertz contact law. The comprehensive information about steady-state and transient dynamic properties of PVDF membranes obtained in this study is expected to contribute to the further development of the PVDF piezoelectric element.